Using decision science to evaluate global biodiversity indices. Issue 2 (2nd September 2020) - Watermeyer, Kate E.; Guillera‐Arroita, Gurutzeta; Bal, Payal; Burgass, Michael J.; Bland, Lucie M.; Collen, Ben; Hallam, Chris; Kelly, Luke T.; McCarthy, Michael A.; Regan, Tracey J.; Stevenson, Simone; Wintle, Brendan A.; et al.
Abstract: Global biodiversity indices are used to measure environmental change and progress toward conservation goals, yet few indices have been evaluated comprehensively for their capacity to detect trends of interest, such as declines in threatened species or ecosystem function. Using a structured approach based on decision science, we qualitatively evaluated 9 indices commonly used to track biodiversity at global and regional scales against 5 criteria relating to objectives, design, behavior, incorporation of uncertainty, and constraints (e.g., costs and data availability). Evaluation was based on reference literature for indices available at the time of assessment. We identified 4 key gaps in indices assessed: pathways to achieving goals (means objectives) were not always clear or relevant to desired outcomes (fundamental objectives); index testing and understanding of expected behavior was often lacking; uncertainty was seldom acknowledged or accounted for; and costs of implementation were seldom considered. These gaps may render indices inadequate in certain decision‐making contexts and are problematic for indices linked with biodiversity targets and sustainability goals. Ensuring that index objectives are clear and their design is underpinned by a model of relevant processes are crucial in addressing the gaps identified by our assessment. Uptake and productive use of indices will be improved if index performance is tested rigorously and assumptions and uncertainties are clearly communicated to end users. This will increase index accuracy and value in tracking biodiversity change and supporting national and global policy decisions, such as the post‐2020 global biodiversity framework of the Convention on Biological Diversity. Abstract : Article impact statement : Evaluating biodiversity indices against criteria testing fitness for use means more effective and robust application in decision making. Abstract : Uso de las Ciencias de la Decisión para Evaluar los Índices Globales de Biodiversidad Resumen: Los índices globales de biodiversidad se usan para medir el cambio ambiental y el avance hacia los objetivos de conservación, aunque pocos han sido evaluados completamente en cuanto a su capacidad para detectar las tendencias de interés como las declinaciones de especies amenazadas o la función del ecosistema. Evaluamos cualitativamente nueve índices de uso común para dar seguimiento a la biodiversidad a escala global y regional contra cinco criterios relacionados con los objetivos, diseño, comportamiento, incorporación de la incertidumbre y restricciones (p. ej.: costos y disponibilidad de datos) mediante una estrategia estructurada basada en las ciencias de la decisión. La evaluación se basó en la literatura de referencia para los índices disponibles al momento del análisis. Identificamos cuatro vacíos importantes en los índices estudiados: las vías para lograr los objetivos (objetivos medios) no fueron siempre claras o relevantes para los resultados deseados (objetivos fundamentales); el análisis del índice y el entendimiento del comportamiento esperado casi siempre fueron escasos; pocas veces se consideró o explicó la incertidumbre; y casi nunca se consideraron los costos de la implementación. Estos vacíos pueden hacer que los índices sean inadecuados en ciertos contextos de toma de decisiones y son problemáticos para los índices vinculados a los objetivos de biodiversidad y las metas de sustentabilidad. Es de suma importancia asegurarse que los objetivos del índice sean claros y que su diseño esté respaldado por un modelo de procesos relevantes para tratar con los vacíos identificados en nuestro estudio. La aceptación y el uso productivo de los índices mejorarán si el desempeño del índice es evaluado rigurosamente y las suposiciones e incertidumbres se les comunican claramente a los usuarios finales. Lo anterior aumentará la precisión y valor del índice en el seguimiento de los cambios de la biodiversidad y en el apoyo a las decisiones políticas nacionales y mundiales, como el marco de trabajo para la biodiversidad post‐2020 establecido por la Convención sobre la Diversidad Biológica. 摘要: 全球生物多样性指数被用于衡量环境变化和保护目标的进展情况, 然而, 很少有研究全面评估这些指数监测相应变化 (如受威胁物种的数量下降或生态系统功能丧失) 的能力。本研究利用基于决策科学的结构化方法, 根据目标、设计、行为、不确定性和约束因素 (如成本和数据可用性) 这五个标准, 定性地评估了九个常用于追踪全球和区域生物多样性的指数。我们以评估阶段已有的参考文献为基础, 在被评估的指数中找出了四个关键的差距:实现目标的途径 (方法目标) 有时不够清晰或与预期结果 (基本目标) 不相关;缺乏检验和理解预期行为的指数;很少考虑或解释不确定性;很少考虑实施成本。这些不足可能导致某些决策背景下指数使用不恰当, 或是与生物多样性目标和可持续性目标相关的指数存在问题。要解决我们在评估中发现的差距, 应确保指数的目标清晰, 且设计基于相关过程的模型。如果能严格检验指数的表现情况, 并向最终使用者清楚地传达其假设和不确定性, 则能改进对指数的理解和有效使用。这样将提高在追踪生物多样性变化、支持国家和全球政策决策 (如《生物多样性公约》 2020 年后全球生物多样性框架) 中指数的准确性和价值。翻译: 胡怡思; 审校: 聂永刚